Whatever Became of Child's Play?. Issue 1 (1st January 2017) - Wright, Brett A.; Schwab, Keri A.; Dustin, Daniel L.
Abstract: The history of parks and recreation is deeply rooted in child's play. From Joseph Lee's writings about the developmental benefits of child's play at the beginning of the 20 th century to the establishment of the University of Illinois's Motor Performance and Play Research Laboratory in the 1960s and 1970s, child's play has been a central focus of our field's leading philosophers, scholars, and practitioners. However, of late, the topic of child's play has all but disappeared from our literature. The question we ask in this paper is "why?" What we conclude from our questioning is both good and bad news for parks and recreation. The good news is that our field was clearly ahead of its time in appreciating the critical contributions of child's play to human growth and development. The bad news is that, somewhere along the line, we seem to have lost interest in the subject. Meanwhile, academicians in other fields are now beginning to appreciate, research, and write about the significance of child's play, and they are replacing park and recreation professionals as leading advocates for the importance of child's play in human growth and development. We conclude our paper by discussing what we can and should learn from this turn of events.